2017
DOI: 10.1080/09638288.2017.1401675
|View full text |Cite
|
Sign up to set email alerts
|

Fair or square? Experiences of introducing a new method for assessing general work ability in a sickness insurance context

Abstract: The perceived fairness and social validity of the assessment depended on how it was carried out; organisational conditions and priorities; communication skills; and decision outcomes. Professionals have an important pedagogical task in explaining the purpose and procedure of the assessment in order for the sick-listed to perceive it as fair rather than square, i.e., too standardised and not considering individual conditions. If the assessment could be used also for rehabilitative purposes, it could possibly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 33 publications
4
27
1
1
Order By: Relevance
“…This pathogenic nature of interactions is related to the inability of systems to respond to needs among different claimant groups, and we see a cyclical pattern involving legitimacy concerns, adversarial relations, difficulties in getting diagnoses and treatment, chronicity of injuries and psychological consequences [8]. A similar lack of perceived legitimacy was found related to work ability assessments in the Swedish social insurance system [7], and related to contacts with system representatives [9]. The negative effects of compensation systems on claimants' health has been reported in different jurisdictions (e.g., [10]), and it has been concluded that systems that succeed in reducing adversarial interactions stand better chances of preserving the dignity of workers [2].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…This pathogenic nature of interactions is related to the inability of systems to respond to needs among different claimant groups, and we see a cyclical pattern involving legitimacy concerns, adversarial relations, difficulties in getting diagnoses and treatment, chronicity of injuries and psychological consequences [8]. A similar lack of perceived legitimacy was found related to work ability assessments in the Swedish social insurance system [7], and related to contacts with system representatives [9]. The negative effects of compensation systems on claimants' health has been reported in different jurisdictions (e.g., [10]), and it has been concluded that systems that succeed in reducing adversarial interactions stand better chances of preserving the dignity of workers [2].…”
Section: Introductionsupporting
confidence: 52%
“…Several studies have indicated how contact with such systems may be perceived as cumbersome or even have negative health effects [1][2][3][4][5], and that people with fewer resources risk being mistreated or offered worse service [6]. Previous studies have also indicated how eligibility assessments (e.g., work ability assessments) require adequate communication from professionals in the system in order for claimants to consider the assessment to have social validity, i.e., the extent to which it is considered acceptable or legitimate [7]. Hence, the actual outcomes and perceptions of a benefit claim may be influenced by the quality of medical certificates but also by the differences in resources among individual claimants, as well as the insurance organization's competence and skills in managing such differences.…”
Section: Introductionmentioning
confidence: 99%
“…Insurance officials considered the self-report part of the assessment made for a more participatory and hence more fair assessment, one of the physicians claimed that there were problems with self-reports, since they could lead to an overestimation of abilities. The people on sick leave, on the other hand, did not generally seem to consider their self-report as particularly important for their perception of fairness of the assessment [13].…”
Section: Ethical Considerationsmentioning
confidence: 87%
“…There are several other similar concepts related to or interchangeable with work ability. Work capacity has been used synonymously [9,10] and also capacity to work [11] work limitations [12], activity capacity [13] and work functioning [14]. These concepts are usually described in a context of using a certain measure, usually a self report instrument, observation protocol or a test procedure.…”
Section: Imentioning
confidence: 99%
“…First required is a medical certificate from a physician. After 180 days of sickness absence, the social insurance official may order an extended assessment (AFU) [16], which includes a selfreport questionnaire, an assessment by a physician (who is not the treating physician), and (depending on whether considered necessary) assessments by a physiotherapist, an occupational therapist and/or a psychologist. These assessments are performed at specific rehabilitation centers by personnel trained in the assessment procedure.…”
Section: Methodsmentioning
confidence: 99%